Optimization of Solid-State Fermentation with Lactobacillus brevis and Aspergillus oryzae for Trypsin Inhibitor Degradation in Soybean Meal - You-ling GAO; Cai-sheng WANG; Qiu-hua ZHU; Guo-ying QIAN (Journal of Integrative Agriculture)
The aim of the present study was to optimize trypsin inhibitor degradation in soybean meal by solid-state fermentation (SSF) with Lactobacillus brevis and Aspergillus oryzae, and to determine the effect of SSF on phytic acid, crude protein, crude fat, and amino acid profile. Response surface methodology (RSM) with Box-Behnken design was used to optimize SSF. The optimal conditions derived from RSM for L. brevis fermentation were: pH=5.1; inoculum size=10%; duration=72 h; substrate to water ratio=1.5. The minimum content of trypsin inhibitors was 6.4 mg g−1 dry matter. The optimal conditions derived from RSM for A. oryzae fermentation were: substrate to water ratio= 0.81; inoculum size=4%; duration=120 h. The minimum content of trypsin inhibitors was 1.6 mg g−1 dry matter. Both L. brevis and A. oryzae decreased trypsin inhibitors dramatically (57.1 and 89.2% respectively). L. brevis fermentation did not affect phytic acid (0.4%) and crude fat (5.2%) considerably, whereas A. oryzae fermentation degraded phytic acid (34.8%) and crude fat (22.0%) contents to a certain extent. Crude protein content was increased after both fermentation (6.4 and 12.9% for L. brevis and A. oryzae respectively). Urease activity was reduced greatly (83.3 and 58.3% for L. brevis and A. oryzae respectively). In conclusion, SSF with A. oryzae and L. brevis reduced trypsin inhibitor content and modified major macronutrients in soybean meal.